1990
DOI: 10.1111/j.1752-1688.1990.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

CHANGING RAINFALL‐RUNOFF RELATIONSHIPS IN THE URBANIZING PEACHTREE CREEK WATERSHED, ATLANTA, GEORGIA1

Abstract: Peachtree Creek is a gaged watershed that has experienced a substantial increase in urbanization. The relationships of runoff to rainfall were studied for total annual flows, low flows, and peak flows. For each type of flow the relationship in the later, more urbanized period was compared to that in the earlier, less urbanized period. An increase in total runoff in wet years was observed as urbanization increased, but a decrease occurred during dry years. For low flows a similar decrease of runoff in dry years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 7 publications
1
56
0
Order By: Relevance
“…Bonta et al (1997) investigated the changes in Natural Resources Conservation Service (NRCS) curve number, flow-duration curve and peak flow for differing periods of pre-mining, mining reclamation and post-reclamation in three small experimental watersheds in Ohio, USA. Additionally, Ferguson and Suckling (1990) applied polynomial regressive equations of impervious surfaces to analyse the relationship of runoff to rainfall for total annual flows, low flows and peak flows. Furthermore, Tsihrintzis and Hamid (1997) used the Soil Conservation Service (SCS) curve number method and empirical equations developed by the U.S. Environmental Protection Agency (EPA) to compute runoff depth and pollutant loading of urban stormwater runoff from four small sites with different predominant land uses, including low-density residential, high-density residential, highway and commercial, in South Florida, USA.…”
Section: Review Of Related Researchmentioning
confidence: 99%
“…Bonta et al (1997) investigated the changes in Natural Resources Conservation Service (NRCS) curve number, flow-duration curve and peak flow for differing periods of pre-mining, mining reclamation and post-reclamation in three small experimental watersheds in Ohio, USA. Additionally, Ferguson and Suckling (1990) applied polynomial regressive equations of impervious surfaces to analyse the relationship of runoff to rainfall for total annual flows, low flows and peak flows. Furthermore, Tsihrintzis and Hamid (1997) used the Soil Conservation Service (SCS) curve number method and empirical equations developed by the U.S. Environmental Protection Agency (EPA) to compute runoff depth and pollutant loading of urban stormwater runoff from four small sites with different predominant land uses, including low-density residential, high-density residential, highway and commercial, in South Florida, USA.…”
Section: Review Of Related Researchmentioning
confidence: 99%
“…Paul and Meyer (2001) also found that urbanizing watersheds exhibit a larger volume of the received precipitation as surface runoff and less as groundwater flow. Warner (1984), and Ferguson and Suckling (1990) concluded that low flows in urbanized watersheds have a tendency to diminish due to the effects of impervious surfaces by limiting infiltration and enhancing evaporation. However, several other studies (Hollis, 1977;Konrad et al, 2002;Meyer, 2005) have documented increasing low flows from urbanization alone.…”
Section: Introductionmentioning
confidence: 98%
“…People mainly dwell in the downstream area of a basin, and tribal societies or cities often develop according to the living quality of the environment. The development of an urban area within a watershed causes a drastic change of land use and has major effects on the functioning of the hydrological status of that area during flood conditions (Simmons and Reynolds, 1982;Ferguson and Suckling, 1990;Leopold, 1991;Sala and Inbar, 1992;Singh, 1998;Gremillion et al, 2000).…”
Section: Introductionmentioning
confidence: 99%